Relationship Of Workload And Work Stress Of Nurses To Hand Hygiene Compliance During The Covid-19 Pandemic At Porsea Hospital - Dosmaida Nababan (Institute of Computer Science (IOCS), 2021)
Nurses play a major role in infection prevention and control. Hand hygiene is recognized as the most effective measure in preventing and controlling the spread of infection in health facilities. The outbreak of COVID-19 has caused a fairly high spread of the virus, in this situation hand hygiene has a very important role. Nurses' workload and work stress affect nurses' hand hygiene compliance. The purpose of this study was to analyze the relationship between workload and work stress of nurses with hand hygiene compliance during the COVID-19 pandemic at Porsea Hospital. This research is a quantitative research with analytical descriptive using cross sectional. The sampling technique used was total sampling with a total of 22 respondents who participated in this study. Chi-square test was used to analyze the data. The results of this study indicate that there is a significant relationship between workload (P value = 0.008) and work stress (P value = 0.006) of nurses with hand hygiene compliance. Hospital management needs to be able to carry out continuous evaluation and training to increase nurses' self-awareness in the application of hand hygiene. Nursing leaders need to know the physical and emotional conditions of nurses in working during the COVID-19 pandemic.